Young people, students, and athletes: competition redefined in contexts of intensified schooling in sports - Fuentes, Sebastián Gerardo (2025)
Based on an ethnography carried out in an Argentinean high school that is located in a sports club and oriented to physical education, this article analyzes appropriations of sport by young people in terms of their school experiences, related competition, curriculum, and aspirations. Techniques such as semi-structured interviews, field observations, and norm analysis were used. It was found that students contextually appropriate available, legitimate, or dominant meanings and practices regarding norms/regulations coming from school, sports, or even adult expectations, produce alternative or slightly transformed values. They build a critical relationship with the curriculum, with sports, and with the school itself, signifying in a different way the emergence of sports competition values (based on individual success) and the enrichment of the cultural production of the educated person in a more collective way. For many students, sports are valued as a place to develop a professional career, but they are also in tension with youth, student, and curriculum expectations. Sports in these types of schools provide an appealing experience for young people, helping the institution meet their objectives by offering valuable knowledge, discipline, and companionship.